The Effect of Investment Knowledge on Investment Decisions of FEB Students at Investment Gallery FEB Upgris With Financial Literacy and Financial Behavior As Intervening Variables - Prabowo, Heri; Mustafida, Devi; Kurniawan, Bayu (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This study aims to analyze the effect of investment knowledge on investment decisions of FEB UPGRIS students with financial literacy and financial behavior as intervening variables. The research method used is the quantitative method. This study's sample number was 88 respondents using the survey method technique. The data is used using an online questionnaire with the help of the google docs application, which is distributed to each student with an Open Account at the Investment Gallery FEB UPGRIS. The results of this study indicate that 1) Investment knowledge variables and financial behavior affect the investment decisions of FEB students at the Investment Gallery FEB UPGRIS, 2) Investment knowledge affects the financial literacy of FEB students at the FEB UPGRIS investment gallery, 3) Investment knowledge affects the financial behavior of students FEB in the FEB UPGRIS Investment Gallery, 4) while the financial literacy variable does not affect the investment decisions of FEB students in the FEB UPGRIS Investment Gallery. 25) Financial behavior affects the investment decisions of FEB students in the FEB UPGRIS investment gallery, 6) Investment knowledge does not affect the investment decisions of FEB students in the FEB UPGRIS investment gallery through financial literacy, and 7) Investment knowledge affects the investment decisions of FEB students in the investment gallery FEB UPGRIS through financial behavior. The results of this study show that financial behavior formed from investment knowledge increasingly convinces students to invest in the Investment Gallery FEB UPGRIS. Keywords: investment decisions, investment knowledge, capital markets